Croce as Reviewer of Simmel’s War Writings - Picchio, Marta (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2017)
This essay comments on Benedetto Croce’s review of Der Krieg und die geistigen Entscheidungen. After illustrating Croce and Simmel’s opposing philosophical visions of the Great War, light will be thrown on the reviewer’s manipulative choices made to crush his colleague’s intellectual stature and writings. Croce’s was a prejudiced attitude that ignored the deeply felt evolution of Simmel’s thought in the course of the conflict: from his enthusiastic support of the national war effort, manifested in 1914, to the subsequent anguished and critical eye when he perceived that Europe had set out on the road to civil and cultural suicide.